Sociologia de um maldito : a obra de Jards Macalé na ditadura militar brasileira - Lima, Mathêus Sampaio da Silva (2024)
Resume: This work aims to analyze the work of Jards Macalé, especially his production between 1969 and 1980. This section covers Jards' most significant production during the period of the military dictatorship. The idea is to analyze the relationships between the cultural industry and art in this period, the modes of resistance and interpretations and the avant-garde meanings for such a Brazilian context. Through Jards' songs, the process of solidification of a cultural industry is interpreted in which political art, as a project that was at the service of a radical transformation of Brazilian society, is exhausted, this political art project can be crystallized in the desired ways in the 1960s by organizations such as the Centros de Cultura Popular - CPC of the União Nacional dos Estudantes – UNE, other political and social projects present at the time can also be interpreted as the cosmopolitan vision found in the tropicalismo, who had as their line the union between the modern and traditional in an internationalized world, opposing a nationalist reading such as that of the CPC. Another project found was the presentist counterculture that can be seen in Novos Baianos, in which the idea of planning for the future is suspended, what can be done is to live in the here and now. In Jards' work, a project with diffuse dimensions was found, as it is based on the negativity of the world, without there being a schematic guidance on what to do, but it stands as a moment of elaboration on the existing world, considering the previous moments of the Brazilian music., in this sense Jards is a promoter of a reflexivity on the period that sought to overcome a naive conscience and demonstrated in the desire for an open future the possibility of a world that can be both beautiful and morbid, thus Jards can be seen as an artist who presents the elements of barbarism in a Brazil that has a growing cultural industry and a dictatorial military government. Finally, Jards was evaluated as an artist who persists in the idea of avant-garde art, by criticizing the modes of art production of his time and consequently the social world, in this sense Jards was seen as a neo-avant-garde for persisting in the meanings avant-garde in a different era from historical avant-gardes.